Indentation crack formation and interaction on pure and metallised Si wafers - Su, Dan. (2008)
The metallization of Si represents an important industrial process and produces a bi-layered composite of a ductile metal film on a brittle substrate. The mechanical properties of such a composite are determined by the properties of the two layers and the interface and influenced by the fact that the metalized layer, being a very thin film, possesses properties different from those of a bulk material. The fracture toughness is also influenced by the nature and distribution of defects which may be generated during use of these materials, even if the manufacturing process produces a reasonably defect free material. Indentation cracking has been extensively used for the measurement of fracture toughness due to its small sample size requirements as well as a relatively good correlation with values obtained from traditional fracture mechanics tests. The indentation process, with its associated cracks, produces permanent plastic deformation and also introduces a residual stress field. This field influences the crack pattern generated in an adjacent indent and can be used as a methodology to model the influence of multiple defect sources.